2009
DOI: 10.1002/dev.20389
|View full text |Cite
|
Sign up to set email alerts
|

Fetal motor activity and maternal cortisol

Abstract: The contemporaneous association between maternal salivary cortisol and fetal motor activity was examined at 32 and 36 weeks gestation. Higher maternal cortisol was positively associated with the amplitude of fetal motor activity at 32 weeks, r(48) = .39, p < .01, and 36 weeks, r(77)=.27, p < .05, and the amount of time fetuses spent moving at 32 weeks during the 50 minute observation period, r(48) = 33, p < .05. Observation of periods of unusually intense fetal motor activity were more common in fetuses of wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 47 publications
2
39
0
3
Order By: Relevance
“…This finding is consistent with two prior studies [12,13] but contrary to most indicating no significant sex differences in fetal activity [2,[14][15][16][17]. Given that all of these studies were based on samples of less than one hundred while the present study was derived from a sample of more than six and a half thousand, the inconsistency may be attributed to the much greater statistical power in the present study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with two prior studies [12,13] but contrary to most indicating no significant sex differences in fetal activity [2,[14][15][16][17]. Given that all of these studies were based on samples of less than one hundred while the present study was derived from a sample of more than six and a half thousand, the inconsistency may be attributed to the much greater statistical power in the present study.…”
Section: Discussionsupporting
confidence: 91%
“…While two of these studies reported that male fetuses were more active than female fetuses [12,13], the majority have indicated that the differences are non-significant [14][15][16][17]. It is important to note that all of these studies were based on samples of less than one hundred pregnant women and that the time during which each woman was monitored with ultra sound were typically less than two hours.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of findings relate exposure to elevated maternal cortisol to a neurobehavioral risk profile including greater stress reactivity at birth and infant fussiness in the first months of life (Davis, Waffarn, & Sandman, 2010; de Weerth, van Hees, & Buitelaar, 2003; Werner et al, 2013). In the few fetal studies considering maternal cortisol as a possible influence on fetal development, associations were found between concurrently tested elevations and greater movement at 32–36 gestational weeks (DiPietro et al, 2009) and higher overall FHR at 36–38 weeks (Monk et al, 2004). Using a longitudinal study design, Glynn and Sandman (2012) showed lower cortisol early in pregnancy was associated with precocious development indexed by mounting a motor response to a vibro acoustic stimulus (Glynn & Sandman, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…DiPietro et al [51] verified, in a sample of 52 mothers and fetuses, assessed at 24, 30, and 36 weeks of gestation, that the fetuses of more emotional women, assessing their lives as more stressful and signalizing more difficulties during pregnancy, were more active, than those of mothers who perceived their pregnancy with positive emotionality. Mediation mechanisms involving stress hormones, the HPA axis and role of the placenta have been proposed to explain the association between maternal psychological symptoms and fetal behavior [83,84].…”
Section: Discussionmentioning
confidence: 99%